2021
DOI: 10.3390/jmse9121455
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Spatial Phytoplankton Variability during Spring with Eutrophic Inshore and Oligotrophic Offshore Waters in the East Sea, Including Dokdo, Korea

Abstract: The area near the subpolar front of the East Sea has high primary productivity during the spring season. We conducted two surveys, one in early spring and another in late spring, to assess environmental factors that influence phytoplankton community structure during these times. During early spring, vertical mixing supplied abundant nutrients to the surface. Due to the well-mixed water column, there were high nutrient levels, but total phytoplankton abundances and diversity were relatively low and were dominat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
(105 reference statements)
0
6
0
Order By: Relevance
“…Eutrophication and surface warming pose significant threats to marine ecosystems, as evidenced by multiple studies (Laurent et al, 2018;Deininger and Frigstad, 2019;Freeman et al, 2019;Wei et al, 2022). The influence of nutrients on the phytoplankton community is widely acknowledged (Irwin et al, 2006;Song et al, 2016;Cloern, 2018;Lee et al, 2021). The findings from the CCA and ABT analyses provide further confirmation that seasonal variation in the phytoplankton community are primarily driven by nutrient levels (Figures 6 and 7B).…”
Section: Nutrient Regime and Water Temperature Dynamics In The Smbmentioning
confidence: 54%
“…Eutrophication and surface warming pose significant threats to marine ecosystems, as evidenced by multiple studies (Laurent et al, 2018;Deininger and Frigstad, 2019;Freeman et al, 2019;Wei et al, 2022). The influence of nutrients on the phytoplankton community is widely acknowledged (Irwin et al, 2006;Song et al, 2016;Cloern, 2018;Lee et al, 2021). The findings from the CCA and ABT analyses provide further confirmation that seasonal variation in the phytoplankton community are primarily driven by nutrient levels (Figures 6 and 7B).…”
Section: Nutrient Regime and Water Temperature Dynamics In The Smbmentioning
confidence: 54%
“…was dominant in the whole water column (Figure 5), and this diatom positively correlated with nutrients in the PCA analysis (Figure 8). Lee et al [14] reported that Chaetoceros species, such as C. socialis, tend to thrive under low water temperatures when nutrients are abundant in the euphotic layers of the East Sea, Korea. Additionally, Thompson et al [3] and Lee et al [14] reported that the influx of abundant nutrients into the euphotic layers during winter mixing coincided with a high biomass and reproduction of diatoms.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [14] reported that Chaetoceros species, such as C. socialis, tend to thrive under low water temperatures when nutrients are abundant in the euphotic layers of the East Sea, Korea. Additionally, Thompson et al [3] and Lee et al [14] reported that the influx of abundant nutrients into the euphotic layers during winter mixing coincided with a high biomass and reproduction of diatoms. In addition, the predominant of this diatom in winter led to a relatively lower diversity (H') in the whole water layer compared to other seasons (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations